Unwitnessed head trauma: the bamboo did it. Issue 12 (24th October 2016) - Sousa, Rodrigo; Luz, Ângela; Abecasis, Francisco; Vieira, Marisa
Key Clinical Message: Unwitnessed penetrating head injuries (PHIs) are often challenging. The inability to locate a foreign body should not exclude this diagnosis nor should it delay treatment. Attempts must be made to clarify the mechanism of injury, as this may allow for a better understanding of the patient's condition. Abstract : Unwitnessed penetrating head injuries (PHIs) are often challenging. The inability to locate a foreign body should not exclude this diagnosis nor should it delay treatment. Attempts must be made to clarify the mechanism of injury, as this may allow for a better understanding of the patient's condition.